2003
DOI: 10.2337/diacare.26.2.349
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Retinopathy 10 Years After Diagnosis in Young Adult People With Diabetes

Abstract: OBJECTIVE—To estimate the prevalence and severity of diabetic retinopathy (DR) 10 years after diagnosis in a nationwide population-based cohort study of young adult diabetic patients in Sweden. RESEARCH DESIGN AND METHODS—The Diabetes Incidence Study in Sweden (DISS) aims to register all incident cases of diabetes aged 15–34 years in Sweden. In 1987–1988, 806 cases were reported, and 627 (78%) of them were followed up with regard to retinopathy 8–10 years later. The assessment was based on retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 32 publications
(14 reference statements)
10
89
1
4
Order By: Relevance
“…For example, the cumulative incidence of retinopathy in fulminant type 1 diabetic patients was 9.8%, significantly higher than the 0% in type 1A patients. The high incidence is notable compared with the result of the nationwide population-based Diabetes Incidence Study in Sweden (DISS) [11]. DISS resembled our study because all patients were adolescents and adults who were followed from disease onset and had mean HbA 1c of 7.5% at follow-up.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…For example, the cumulative incidence of retinopathy in fulminant type 1 diabetic patients was 9.8%, significantly higher than the 0% in type 1A patients. The high incidence is notable compared with the result of the nationwide population-based Diabetes Incidence Study in Sweden (DISS) [11]. DISS resembled our study because all patients were adolescents and adults who were followed from disease onset and had mean HbA 1c of 7.5% at follow-up.…”
Section: Discussionsupporting
confidence: 51%
“…This classification corresponds to levels 10, 21/10 to 31/31, 41/<41 to 51/51 and 60+/<60+ to 60+/60+, as defined in the Wisconsin study [9][10][11]. Retinopathy was defined as the appearance of SDR or more severe grade in one eye.…”
Section: Subjectsmentioning
confidence: 99%
“…Over recent decades, diabetes care has improved in terms of decreased mean HbA 1c and mean systolic blood pressure [8], changes that have been shown to have a preventive effect on diabetic complications [32,33]. Previous research [34,35] has shown a similar effect on the incidence of DR in Sweden. However, for type 2 diabetes, this explanation is contradicted by two Swedish population-based studies from the same time period [25,36].…”
Section: Discussionmentioning
confidence: 74%
“…The prevalence of DR in type 1 diabetic patients is very high (;90% after 15 years of disease duration), as shown by long-term epidemiological studies (2). Among the several known risk factors for DR development, disease duration is indeed one of the most relevant (3)(4)(5)(6), together with metabolic control (5,7). Nevertheless, a fraction of patients presenting good metabolic control (;10%) do develop DR, and still another proportion of patients with poor metabolic control, nevertheless, do not develop this complication (8).…”
mentioning
confidence: 95%